Avaliação do exopolissacarídeo kefiran: ensaio in vitro da atividade antimicrobiana em cepas de Candida albicans e modelagem molecular das interações com nutrientes e receptor TLR-4 - Laudelina Ferreira de Andrade (2025)
Kefiran, an exopolysaccharide produced by microorganisms present in kefir grains, has garnered increasing interest due to its bioactive properties and potential biotechnological applications. This study aimed to obtain and characterize kefiran, evaluating its antimicrobial activity against two isolates of Candida albicans: a clinical strain from the Culture Collection of the Mycotheca of the Department of Mycology at UFPE (URM 4986) and a reference strain from the American Type Culture Collection (ATCC 60193). Additionally, the study sought to investigate its molecular interactions with nutrients and the immune system through the TLR4-MD2 complex. Kefiran extraction was performed according to the adapted protocol of Martins et al. (2022). Kefir grains were suspended in distilled water and heated at 90°C for 1 hour under continuous agitation, followed by centrifugation and precipitation in ethanol. The extraction and purification process was carried out over five days to obtain the exopolysaccharide under optimal conditions for subsequent analyses. Antifungal activity was assessed through in vitro assays, including the disk diffusion test and determination of the Minimum Inhibitory Concentration (MIC) using the microdilution method in plates. In addition to biological assays, computational analyses were performed using molecular dynamics simulations and molecular docking to investigate kefiran's interactions with nutritional compounds such as vitamins, amino acids, saccharides, triacylglycerol, and the TLR-4 receptor. The choice of the Toll-like receptor 4 (TLR-4) and myeloid differentiation factor 2 (MD-2) complex was based on its central role in the immune system. TLRs, key components of innate immunity, are responsible for recognizing pathogen-associated molecular patterns and modulating the immune response. The initial configuration of the simulation boxes was generated using the Packmol software. The systems were energy-minimized and subjected to 60 ns of simulations in the NPT ensemble (298.15 K and 1 atm) using the CHARMM force field and the NAMD software. Molecular docking was employed to evaluate kefiran's affinity for the TLR4-MD2 complex, exploring its immunomodulatory potential. The results confirmed the efficiency of kefiran extraction and purification. The minimal presence of residual proteins in the sample demonstrated the effectiveness of the process. In vitro analyses revealed that kefiran exhibited a fungistatic effect against the Candida albicans ATCC 60193 strain, inhibiting its growth but without fungicidal action. This suggests that its antimicrobial effect may be related to indirect mechanisms, such as modulation of the immune system and microbiota. Molecular modeling results indicated that kefiran interacted with hydrophobic nutrients, such as triacylglycerol (trivalerate), vitamin D (cholecalciferol), and isoleucine, in addition to showing affinity for lipopolysaccharide (LPS) in the TLR4-MD2 system. These interactions suggest that kefiran may modulate immune responses, contributing to its bioactive effects. Thus, this study reinforces the potential of kefiran as a promising bioactive compound with possible therapeutic and biotechnological applications. The integration of microbiological assays with computational approaches provided a more comprehensive understanding of its properties, laying the groundwork for future investigations into its applications in biological systems and the pharmaceutical industry.